An Evaluative Study of Sarva Shikhsha Abhiyan (SSA) in District Anantnag - Khan, Mahmood Ahmad; Koul, Feeroz Ahmad (JOURNAL OF INDIAN EDUCATION, 2011)
The study was undertaken to evaluate the functioning of centrally sponsored scheme Sarva Shikhsha Abhiyan (SSA) in district Anantnag. The sample consists of all the 507 SSA schools of district Anantnag. Self constructed information bank and check list were used for the collection of data and percentage statistics was used for the analysis of data. The results of the study highlight that SSA has opened 507 schools in all the 12 educational zones of district Anantnag with total enrollment of 23590. A total of 1200 teachers have been appointed making overall pupil teacher ratio(PTR) of 1:20 in all the zones of the district Anantnag.There has been 16% increase in enrollment from 2008 to 2009.No provision has been made by the government for toilet and drinking water facilities in majority of these schools .All the education Guarantee scheme (EGS)centers are housed in single rooms donated by education volunteers (EV’S) themselves. 98% of teachers have received training under SSA. The study also reveals that the overall enrollment of Gujjars and Bakerwals is 447 in these SSA schools.